2010
DOI: 10.1016/j.stem.2010.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Pax6 Is a Human Neuroectoderm Cell Fate Determinant

Abstract: SUMMARY The transcriptional regulation of neuroectoderm (NE) specification is unknown. Here we show that Pax6 is uniformly expressed in early NE cells of human fetuses and those differentiated from human embryonic stem cells (hESCs). This contrasts the later expression of Pax6 in restricted mouse brain regions. Knockdown of Pax6 blocks NE specification from hESCs. Overexpression of either Pax6a or Pax6b, but not Pax6 PD, triggers hESC differentiation. However, only Pax6a converts hESCs to NE. In contrast, neit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
415
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 410 publications
(444 citation statements)
references
References 62 publications
27
415
1
1
Order By: Relevance
“…In the mouse embryo, Pax6 is expressed in the neuroectoderm of the FB and hindbrain [64]. In human stem cells PAX6 acts as a determinant of neuroectoderm fate [65][66][67]. Consistently, some expression was detected in hVMl cells, but it was higher in hNSl cells (Fig.…”
Section: Regionalization and Activation Of Developmental Gene Cascadementioning
confidence: 54%
“…In the mouse embryo, Pax6 is expressed in the neuroectoderm of the FB and hindbrain [64]. In human stem cells PAX6 acts as a determinant of neuroectoderm fate [65][66][67]. Consistently, some expression was detected in hVMl cells, but it was higher in hNSl cells (Fig.…”
Section: Regionalization and Activation Of Developmental Gene Cascadementioning
confidence: 54%
“…At 10 and 17 days of neural differentiation, hESC-derived primitive and definitive neuroepthelial (NE) cells with scramble shRNA treatment presented typical columnar NE morphology and were organized into rosettes [36][37][38] (Figure 1D and 1E), similar to the structure of NE cells from WT hESC induction (as discussed below and data not shown). Noticeably, although differentiating hESCs with stable ADAR1 knockdown also formed rosette-like structures, these cells expressed low levels of PAX6, SOX1 and FOXG1 ( Figure 1D and Supplementary information, Table S1), and formed much Table S1.…”
Section: Hescs Lacking Adar1 Exhibited Significant Defects In Eb Formmentioning
confidence: 73%
“…As ADAR1 knockdown has little effect on pluripotency, we then proceeded to study the effect of ADAR1 deficiency on differentiation with a protocol summarized in Supplementary information, Figure S2A [36][37][38]. Briefly, hESCs were induced into the neural lineage by generating EBs followed by culturing in neural medium.…”
Section: Hescs Lacking Adar1 Exhibited Significant Defects In Eb Formmentioning
confidence: 99%
“…Similar species-specific functions of cell fate-specifying factors have been reported previously. For example, Zhang et al [64] demonstrated that PAX6 is a key determinant of neuroectoderm cell fate in hPSCs but is not involved in mouse neuroectoderm specification.…”
Section: Discussionmentioning
confidence: 99%